Risks and benefits of early neutering in dogs: Review - Duarte, Oksana; Giusti Schran, Roberta (Pubvet, 2024)
Early neutering in dogs is a common practice initially aimed at population control and the prevention of behavioral and health issues. The literature suggests that neutering performed before the first year of age may be associated with significant health risks for the animals. Studies show that early neutering can increase the propensity for joint injuries, such as hip dysplasia and cranial cruciate ligament rupture, particularly in larger dogs and certain breeds. Additionally, there is evidence that neutering may elevate the risk of various types of cancer, including hemangiosarcoma, lymphoma, mast cell tumors and osteosarcoma, with the age of neutering and the dog’s sex being critical factors in the development of these conditions. In contrast, early spaying of females has shown to be effective in reducing the risk of mammary tumors, especially when performed before the first or second estrous cycle. However, early neutering may also increase the risk of urinary incontinence in females, necessitating appropriate management and treatment strategies. Behaviorally, neutering can lead to improvements in issues such as urine marking, mounting and escaping, particularly in male dogs. This article discusses the importance of carefully evaluating the optimal timing for neutering, considering each dog’s specific characteristics and the potential risks and benefits associated with the procedure.